2020
DOI: 10.21037/jtd-20-266
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different surgical approaches for anterior mediastinal tumor

Abstract: Background: Different video-assisted thoracoscopic surgery (VATS) approaches may related to heterogeneous clinical outcomes in anterior mediastinal tumor surgery. Herein, we assessed the comparison between the subxiphoid and intercostal approach, and also compare the left versus the right incision in the intercostal approach for anterior mediastinal tumor patients. Methods: Clinical data of patients receiving thoracoscopic anterior mediastinal tumor resection were retrospectively collected. Patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
10
0
4
Order By: Relevance
“…They found that the VAS score was lower in patients who underwent the subxiphoid approach than in the intercostal group. Postoperative drainage time, postoperative drainage volume, and hospitalization time were significantly increased in the left thoracic approach group compared with the right thoracic approach group (6). According to previous reports, the most likely complication of the LA approach is phrenic nerve paralysis, while for the subxiphoid approach, it is dyspnea (18).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…They found that the VAS score was lower in patients who underwent the subxiphoid approach than in the intercostal group. Postoperative drainage time, postoperative drainage volume, and hospitalization time were significantly increased in the left thoracic approach group compared with the right thoracic approach group (6). According to previous reports, the most likely complication of the LA approach is phrenic nerve paralysis, while for the subxiphoid approach, it is dyspnea (18).…”
Section: Discussionmentioning
confidence: 82%
“…Through the LA (intercostal), the thoracoscope the contralateral phrenic nerve and the upper pole of the thymus, increasing the risk of intraoperative damage to phrenic nerve-related blood vessels. On the other hand, the intercostal nerve injury caused by the intercostal incision is inevitable, resulting in chronic postoperative intercostal neuralgia and skin paresthesia in the nerve distribution area (6). Suda et al proposed a surgical approach via the subxiphoid approach, which effectively avoided intercostal nerve injury (7).…”
Section: Original Articlementioning
confidence: 99%
“…More importantly, our study found that SVATS thymectomy significantly reduced the VAS scores of patients on the day, the third day and seventh day after the operation. However, whether uniportal or multiportal surgery, the IVATS approach will cause damage to the intercostal nerve to varying degrees ( 24 ), causing postoperative long-term chest pain and numbness. The SVATS can avoid the injury to the intercostal nerve and reduce the postoperative pain to a great extent, especially within one week after operation ( 18 , 22 , 23 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, we believe that SVATS is more suitable for thymectomy than IVATS. However, Mao et al ( 24 ) and Qiu et al ( 28 ) also pointed out that it should be used with caution for obese patients [body mass index (BMI) greater than 30] and patients with poor cardiac function in SVTAS thymectomy. Because the operation space of the SVATS is small, the excessive mediastinal fat in obese patients may further reduce the operation space and increase the intraoperative risk.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was firstly proposed in 1999 by Kido et al (4), subxiphoid video-assisted thoracic surgery (S-VATS) has become the main approach for anterior mediastinal tumor resection under thoracoscopic surgery. Compared with the intercostal thoracic approach, S-VATS provides a better operative view (6) and reduces the operative time, blood loss, postoperative hospital stay, and postoperative pain (7,8).…”
Section: Introductionmentioning
confidence: 99%